Changes of cell growth and magnetosome biomineralization in Magnetospirillum magneticum AMB-1 after ultraviolet-B irradiation - Wang, Yinzhao; Lin, Wei; Li, Jinhua; Pan, Yongxin (Frontiers in Microbiology, 2013)
Effects of ultraviolet radiation on microorganisms are of great interest in field of microbiology and planetary sciences. In the present study, we used Magnetospirillum magneticum AMB-1 as a model organism to examine the influence of ultraviolet-B (UV-B) radiation on cell growth and magnetite biomineralization of magnetotactic bacteria. Live AMB-1 cells were exposed to UV-B radiation for 60 s, 300 s and 900 s, which correspond to radiation doses of 120 J/m2, 600 J/m2 and 1800 J/m2, respectively. After irradiation, the amounts of cyclobutane pyrimidine dimers and reactive oxygen species of the cells were increased, and cell growth was stunted up to ~170 h, depending on the UV-B radiation doses. The UV-B irradiated cells also produced on average more magnetite crystals with larger grain sizes and longer chains, which results in changes of their magnetic properties.